1961
DOI: 10.2136/sssaj1961.03615995002500010026x
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation Based on Soil Suction Measurements

Abstract: Soil suction (soil moisture tension) from zero to 0.8 bar is explicitly indicated by tensiometers. Higher values can be measured by suitably calibrated soil moisture resistance units. An irrigation program, both as to timing and duration of applications, can be carried out based on day‐to‐day records of soil suction at two or more depths in the root zone of the crop involved. Available moisture depletion is a commonly used basis for recommending irrigation practices. Curves are presented which show that, when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0
2

Year Published

1973
1973
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…Soil moisture tension measurements have been shown to be an efficient means for determining timing and duration of irrigation (10). Turfgrass irrigation by tensiometer controlled systems in California under semiarid conditions provided adequate supplemental water for bermudagrass (Cynodon spp.)…”
mentioning
confidence: 99%
“…Soil moisture tension measurements have been shown to be an efficient means for determining timing and duration of irrigation (10). Turfgrass irrigation by tensiometer controlled systems in California under semiarid conditions provided adequate supplemental water for bermudagrass (Cynodon spp.)…”
mentioning
confidence: 99%
“…In studies on many crops soil water potential has been found to be a major determiner of crop yield (Taylor and Ashcroft, 1972) despite the presence of uncontrolled meteorological factors that also influence plant water stress. Irrigation scheduling according to direct soil water potential measurements by tensiometer has been researched (Richards and Marsh, 1961) and practiced 745 for a number of crops, but available information is minimal for sunflower (Prunty, 1981 ).…”
mentioning
confidence: 99%
“…In this study, sunflower response to soil water potential was evaluated by using the method of Richards and Marsh (10) to schedule irrigations and control the soil water potential at Oakes, North Dakota (1979). The comparison of yield estimation methods was also conducted at Oakes.…”
mentioning
confidence: 99%